Intertemporal land allocation decision under uncertainty and hyperbolic discounting - Wang, Qi (SLU/Dept. of Economics, 2013)
Land is of prime importance for all the activities of human beings, and how to efficiently use the limited land resource has been a crucial issue ever since the earliest times of human society. Uncertainty and irreversibility are important issues related to land use change, and it has been shown by Mäler and Fisher (2005, p590-p592) that the replacement of stochastic variable by its expected value could result in inappropriate land use decisions. Based on the two-period framework of Mäler and Fisher (2005, p590-p592), this study introduces two kinds of discounting schemes, standard exponential discounting and hyperbolic discounting, to their analysis. Hyperbolic discounting is demonstrated by many researches and it can decently illustrate individuals’ time-inconsistent preferences toward future payoffs. The decision rules about land use under both exponential discounting and hyperbolic discounting are illustrated and compared in this thesis. The results have shown that, under hyperbolic discounting, when an immediate reward is generated by converting the land for development, the land will be converted earlier than under standard exponential discounting. In contrast, when an immediate cost is entailed to land conversion, the land will be converted later under hyperbolic discounting.